2014
DOI: 10.1371/journal.pone.0099816
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-Sweetened Beverage Intake and Cancer Recurrence and Survival in CALGB 89803 (Alliance)

Abstract: BackgroundIn colon cancer patients, obesity, sedentary lifestyle, and high dietary glycemic load have been associated with increased risk of cancer recurrence. High sugar-sweetened beverage intake has been associated with obesity, diabetes, and cardio-metabolic diseases, but the influence on colon cancer survival is unknown.MethodsWe assessed the association between sugar-sweetened beverage consumption on cancer recurrence and mortality in 1,011 stage III colon cancer patients who completed food frequency ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
82
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 47 publications
2
82
0
1
Order By: Relevance
“…We also found a positive association between SSD and total mortality only among individuals with greater morbidity at baseline. Interestingly, these findings are consistent with the positive association found with total cancer mortality (26) among cancer survivors. Clearly, more research is needed to understand these complex relationships.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We also found a positive association between SSD and total mortality only among individuals with greater morbidity at baseline. Interestingly, these findings are consistent with the positive association found with total cancer mortality (26) among cancer survivors. Clearly, more research is needed to understand these complex relationships.…”
Section: Discussionsupporting
confidence: 89%
“…The evidence supporting associations between SSD and mortality is only slightly larger (10,25,26,38) . In a large pooling study by Singh and colleagues, global cause-specific population-attributable fractions for SSD were calculated and multiplied by cause-specific mortality estimates which resulted in an estimated 184 000 total deaths, 45 000 CVD deaths and 6450 cancer deaths per year due to SSD intake (25) .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…McCullough et al suggested that ongoing high consumption of red and processed meat before, and after, the diagnosis of colorectal cancer was associated with a 79% increased risk of cancer specific mortality (McCullough et al, 2013). High carbohydrate intake including sugar-sweetened beverages is associated with an increased risk of disease recurrence and mortality (Meyerhardt et al, 2012) (Fuchs et al, 2014).…”
Section: Impact Of Physical Activity On Colorectal Cancer Recurrencementioning
confidence: 99%
“…In addition to dental caries and body weight, excessive sugar consumption from foods and beverages high in added sugars has been associated with an increased risk of type 2 diabetes [de Koning et al, 2011], cardiovascular diseases [Malik et al, 2010;Yu et al, 2018;Keller et al, 2014] cancers [Fuchs et al, 2014;Van Blarigan, and Meyerhardt, 2015;Port et al, 2012] as well as non-alcoholic fatty liver disease [Wijarnpreecha et al,2016]. In addition, emerging research suggest that diet high in sugars may increase the risk of developing dementia such as Alzheimer disease Pase et al, 2017].…”
mentioning
confidence: 99%